Landscape, Religion, and the Supernatural - Egeler, Matthias (Oxford University Press, 2024)
Landscape, Religion, and the Supernatural presents a summa of current and classic theorizing on religion and the supernatural in relationship to the land and develops this theorizing further by confronting it with a rich set of folkloristic and historical data. Focusing on the themes of “time and memory,” “repeating patterns,” “identity formation,” “morality,” “labor,” “playfulness and adventure,” “power and subversion,” “sound,” “emotions,” “coping with contingency,” “home and unhomeliness,” and “nature and environment,” the book engages with a broad range of theoretical concepts and approaches from the interdisciplinary field of landscape theory and the study of religions. It brings this theorizing into dialogue with the rich culture of local storytelling and landscape-related traditional beliefs of the Strandir district of the Icelandic Westfjords. In this rural region, landscape-related traditions have been collected since the early nineteenth century and continue to be important to this day. Confronting this rich heritage with the insights of landscape theory both in and beyond the study of religions allows important new contributions to theorizing landscape and religion, especially when it comes to considering the perspectives on landscape held by rural populations rather than the urban upper classes that have stood in the focus of research to date. The example of the Icelandic Westfjords shows the extreme richness of religious and supernatural approaches to the landscape that can be developed in rural communities, and how they are significantly and characteristically different from the urban perspectives of literature and the arts.